2006
DOI: 10.1590/s0100-879x2006001200015
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk factors in a population of Brazilian schoolchildren

Abstract: Epidemiological and clinical evidence suggests that a judicious diet, regular physical activity and blood pressure (BP) monitoring must start in early childhood to minimize the impact of modifiable cardiovascular risk factors. This study was designed to evaluate BP and metabolic parameters of schoolchildren from Vitória, Espírito Santo State, Brazil, and correlate them with cardiovascular risk factors. The study was conducted on 380 students aged 10-14 years (177 boys, 203 girls) enrolled in public schools. Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
12
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 25 publications
7
12
0
5
Order By: Relevance
“…Similar to other studies in pre-pubertal children162526 no significant difference was found between boys and girls regarding physical and clinical characteristics, indicating that such differences will appear later on during puberty. Our study was performed in pre-pubertal children only, to avoid the confounding influence of sex hormones and fat accumulation on blood pressure and other cardiovascular risk factors.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Similar to other studies in pre-pubertal children162526 no significant difference was found between boys and girls regarding physical and clinical characteristics, indicating that such differences will appear later on during puberty. Our study was performed in pre-pubertal children only, to avoid the confounding influence of sex hormones and fat accumulation on blood pressure and other cardiovascular risk factors.…”
Section: Discussionsupporting
confidence: 88%
“…The prevalence of high blood pressure in our cohort was 14.6%(11.1% with pre-hypertension and 3.5% with hypertension), a figure similar to that found in other African countries such as Egypt,18 South Africa,24 the Seychelles26 and Sudan,28 as wellas non-African countries, including Spain,17 United States,1Canada,29 Argentina25 and Brazil 1627. A study in young adults(18 to 29 years) in Angola,30 however, showed a prevalenceof hypertension of 23%, suggesting a rapid increase in bloodpressure during adolescence and early adulthood…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations